Systematic conservation planning for pelagic fish habitats in the Sulawesi Sea, Indonesia - AMEHR HAKIM; AM AZBAS TAURUSMAN; BUDY WIRYAWAN; ARI PURBAYANTO; REGI DARMAWAN; IRFAN YULIANTO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Hakim A, Taurusman AA, Wiryawan B, Purbayanto A, Darmawan R, Yulianto I. 2026. Systematic conservation planning for pelagic fish habitats in the Sulawesi Sea, Indonesia. Biodiversitas 27 (5): d270513. https://doi.org/10.13057/biodiv/d270513. Mackerel scad (Decapterus macarellus) is a key species in pelagic fisheries, providing substantial economic value while playing an important role in pelagic food webs. However, increasing fishing pressure raises concerns regarding stock sustainability and ecosystem integrity. This study aimed to identify priority areas for offshore pelagic Marine Protected Areas (MPAs) in the Sulawesi Sea, Indonesia, by integrating ecological and socio‑economic information within a systematic conservation planning framework. Spatial analyses of spawning and nursery habitats derived from larval surveys were combined with fishing‑related cost data and analyzed using Marxan to optimize conservation prioritization under four alternative scenarios. The analysis identified four candidate conservation areas (Areas I-IV). Among these, Area IV that located between Sangihe and Talaud Islands, consistently emerged as the highest conservation priority, offering the most favorable balance between high ecological value and low fishing intensity. Area IV covers approximately 599,790.91 ha, with 282,364.82 ha (47.08%) identified as a core conservation zone supporting critical spawning and nursery habitats of D. macarellus. These findings demonstrate the value of integrating larval habitat data with spatial optimization tools to identify cost‑efficient and ecologically robust offshore conservation areas. The approach provides a scientifically grounded framework for offshore pelagic MPA planning and contributes empirical evidence to support ecosystem‑based fisheries management in the Sulawesi Sea.